Unexpected insights into antibacterial activity of zinc oxide nanoparticles against methicillin resistant Staphylococcus aureus (MRSA). Issue 10 (26th February 2018) - Kadiyala, Usha; Turali-Emre, Emine Sumeyra; Bahng, Joong Hwan; Kotov, Nicholas A.; VanEpps, J. Scott
Abstract : Zinc oxide nanoparticles cause marked up-regulation of pyrimidine biosynthesis and sugar metabolism but consistent down-regulation of amino acid synthesis in MRSA, suggesting a previously unrecognized mechanism of action. Abstract : Zinc oxide nanoparticles (ZnO-NPs) are attractive as broad-spectrum antibiotics, however, their further engineering as antimicrobial agents and clinical translation is impeded by controversial data about their mechanism of activity. It is commonly reported that ZnO-NP's antimicrobial activity is associated with the production of reactive oxygen species (ROS). Here we disprove this concept by comparing the antibacterial potency of ZnO-NPs and their capacity to generate ROS with hydrogen peroxide (H2 O2 ). Then, using gene transcription microarray analysis, we provide evidence for a novel toxicity mechanism. Exposure to ZnO-NPs resulted in over three-log reduction in colonies of methicillin resistant S. aureus with minimal increase in ROS or lipid peroxidation. The amount of ROS required for the same amount of killing by H2 O2 was much greater than that generated by ZnO-NPs. In contrast to H2 O2, ZnO-NP mediated killing was not mitigated by the antioxidant, N -acetylcysteine. ZnO-NPs caused significant up-regulation of pyrimidine biosynthesis and carbohydrate degradation. Simultaneously, amino acid synthesis in S. aureus was significantly down-regulated indicating a complex mechanism of antimicrobial action involving multiple metabolic pathways. The results of this study point to the importance of specific experimental controls in the interpretation of antimicrobial mechanistic studies and the need for targeted molecular mechanism studies. Continued investigation on the antibacterial mechanisms of biomimetic ZnO-NPs is essential for future clinical translation.